1977
DOI: 10.1136/gut.18.11.903
|View full text |Cite
|
Sign up to set email alerts
|

Serum bile acids in the diagnosis of hepatobiliary disease.

Abstract: SUMMARY The value of serum bile acids (SBA) in the diagnosis of hepatobiliary disease has been investigated. A modified GLC method was used, with an overall coefficient of variation of + 11 % in the control range. Serum was obtained after a 12 hour fast, and two hours after a fatty meal from 73 patients and 14 control subjects. In controls the total fasting SBA of 2 17 + 0-86 ,umol/l increased significantly (P < 0 001) to 3-81 + 1-14 umol/l after a meal. All icteric patients had raised SBA, but in 23 anicteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(55 citation statements)
references
References 30 publications
4
49
1
1
Order By: Relevance
“…The CDCA concentration required for half-maximal inhibition of 11β-HSD2 in cell lysates (K i approximately 20 µM) (20) and the CDCA concentration required to mediate 50% cortisol-induced nuclear MR translocation in intact cells (50 µM) are in the same range, indicating efficient access of extracellular CDCA to 11β-HSD2. Bile acid concentrations have previously been measured in patients with extrahepatic cholestasis and cirrhosis of various etiologies (30,31). The serum concentrations of CDCA were of the same magnitude in patients with extrahepatic cholestasis and patients with cirrhosis and were within the concentration range sufficient to inhibit 11β-HSD2.…”
Section: Figurementioning
confidence: 92%
“…The CDCA concentration required for half-maximal inhibition of 11β-HSD2 in cell lysates (K i approximately 20 µM) (20) and the CDCA concentration required to mediate 50% cortisol-induced nuclear MR translocation in intact cells (50 µM) are in the same range, indicating efficient access of extracellular CDCA to 11β-HSD2. Bile acid concentrations have previously been measured in patients with extrahepatic cholestasis and cirrhosis of various etiologies (30,31). The serum concentrations of CDCA were of the same magnitude in patients with extrahepatic cholestasis and patients with cirrhosis and were within the concentration range sufficient to inhibit 11β-HSD2.…”
Section: Figurementioning
confidence: 92%
“…The high levels of bile acids in the circulation would be useful references for hepatocellular damages. Liver injury in HCC and chronic liver diseases could also be reflected on the increase of blood bile acids (43). The deregulation of lipids metabolism, lipids peroxidation, and cellular damage were the major metabolic events in the model rats during carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a proportionate reduction in serum deoxycholic acid in patients with all forms of hepatobiliary disease (Makino et al, 1969;Pennington et al, 1977a). Thus the trihydroxy: dihydroxy bile acid ratio, described in earlier studies, is equivalent to the cholic :chenodeoxycholic acid ratio, which will be described as the primary bile acid ratio.…”
Section: Serum Bile Acids and Nature Of Hepatic Diseasementioning
confidence: 86%
“…In both studies the normal range of the primary bile acid ratio was large, and overlapped the values for the different diagnostic groups. Clearcut separation of cirrhotics, from controls, from patients with large duct obstruction, on the basis of this ratio, has recently been reported (Pennington et al, 1977a). Unfortunately, there is no evidence that this ratio, or any other bile acid measurement, can separate patients with intrahepatic cholestasis from those with extrahepatic cholestasis in adult practice.…”
Section: Serum Bile Acids and Nature Of Hepatic Diseasementioning
confidence: 99%